Optimasi Adsorpsi Kompetitif Pewarna Biru Metilena dan Metil Oranye Menggunakan Adsorben Zeolit Alam Ende - Nusa Tenggara Timur (NTT) - Ngapa, Yulius Dala; Ika, Yasinta Embu (Indonesian Journal of Chemical Research, 2020)
Waste from the textile industry is considered as a potential source of environmental pollution, especially water because it contains dangerous dyes. In this research, natural zeolite is used as an effective and efficient alternative adsorbent to overcome pollution caused by methylene blue and methyl orange dyes. Activation of natural zeolite was carried out with 3 M HCl solution and was characterized using X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM). While the methylene blue and methyl orange adsorption processes were studied in variations in the weight of the adsorbent, contact time, and pH. The concentration of dyes left in the solution was observed with Spectrophotometer UV-Vis. The results showed that the adsorption capacity of natural zeolite in absorbing methylene blue was 21.189 mg/g and methyl orange was 18.208 mg/g. The optimum conditions of methylene blue and methyl orange adsorption are achieved with successive adsorbent weights 0.3 g and 0,4 g, successive contact times are 60 minutes and 90 minutes, and successive pH are 6 and 2 respectively. The adsorbent weight factor, contact time, and pH have an effect on the adsorption of methylene blue and methyl orange by natural zeolite from Ende.